Radiation from Slotted Cylinder Embedded in Cylindrical Capped Corner Reflector - Ragheb , Hassan A.; Hassan, Essam E. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
An integral equation is formulated for the current distribution on slotted cylinder placed in a cylindrical capped corner reflector. The moment method is used to obtain the current distribution on the antenna conducting surfaces. The radiation pattern of the antenna is then calculated for different corner angles. Interesting results are obtained for different corner angle. The advantage of this geometry over the traditional corner reflector antenna is that it can be part of a ship or aircraft, in which the slotted cylinder is embedded in a conducting corner.